The Cascode and Cascaded Techniques LNA at 5.8GHz Using T-Matching Network for WiMAX Applications - Abu Bakar, Abu Bakar; Othman, Abdul Rani; Husain, Mohd Nor; Johal, Mohammad Syahrir; Hamidon, Jsam (2012)
This project presents the cascode and cascaded techniques LNA at 5.8GHz using T-matching network applicable for WIMAX application. The amplifier uses FHX76LP Low Noise SuperHEMT FET. The LNA designed used T-matching network consisting of lump element reactive element at the input and the output terminal. The cascode and cascaded low noise amplifier (LNA) produced gain of 52.4dB and noise figure (NF) of 1.3dB. The input reflection (S11) and output return loss (S22) are -19.71dB and -10.07dB respectively. The bandwidth of the amplifier is more than 1.24GHz. The input sensitivity is compliant with the IEEE 802.16 standards.